The influence of preoperative dialysis on survival after continuous-flow left ventricular assist device implantation. (30th December 2021) - Lamba, Harveen K; Musfee, Fadi I; Chatterjee, Subhasis; Nair, Ajith P; Civitello, Andrew B; Simpson, Leo; Frazier, O H; Letsou, George V
Abstract:  : OBJECTIVES: Dialysis is considered a contraindication to continuous-flow left ventricular assist device (CF-LVAD) implantation. We evaluated clinical outcomes and survival in carefully selected, low-risk patients with renal failure who required dialysis before CF-LVAD implantation. METHODS: We extracted medical record data of patients who underwent CF-LVAD placement at our centre between 1 January 2006 and 31 August 2017, with 2 clinical scenarios: those who required long-term (>14 days) dialysis and those who required short-term (≤14 days) dialysis immediately before implantation. Demographic, clinical and intraoperative characteristics and survival outcomes were assessed. RESULTS: Of 621 patients who underwent CF-LVAD implantation during the study period, 31 underwent dialysis beforehand. Of these, 17 required long-term dialysis (13 haemodialysis, 4 peritoneal dialysis), and 14 underwent short-term haemodialysis. Compared with the long-term dialysis patients, the short-term dialysis patients were more likely to be Interagency Registry for Mechanically Assisted Circulatory Support profile 1–2 (92.9% vs 70.6%; P  <   0.001), to have needed preoperative mechanical circulatory support (78.6% vs 70.6%; P  <   0.01) and to have higher in-hospital mortality (85.7% vs 29.4%; P  =   0.01). Patients stable on long-term dialysis had acceptable overall survival and markedly better 6-month and 1-year survival than those with short-term dialysis before implantation (64.7% vs 14.3% and 58.8% vs 7.1%, respectively; P  <   0.001). CONCLUSIONS: Carefully selected patients who are stable on long-term dialysis have acceptable survival rates after CF-LVAD implantation. Patients with acute renal failure had much poorer outcomes than those with chronic end-stage renal disease. Abstract : Continuous-flow left ventricular assist devices (CF-LVADs) are commonly used in patients with end-stage heart failure as a bridge to cardiac transplant or as destination therapy for those who do not qualify for cardiac transplant.